Histomorphological study of the Miebomian glands in local Iraqi breed goats (Coprus hircus) - Al-Rikabi, Ahmed Sh. J. (The Iraqi Journal of Veterinary Medicine, 2015)
The study was designed to investigate the histomorphology of Miebomian gland in local Iraqi breed goats (coprus hircus).The research work included specimens of upper and lower eyelids of the eyes of 10 head of local breed black Iraqi goats aged 10-14 months (5 male and 5 female) and the routine histological technique was done from fixation till staining of histological sections. The study revealed that the Miebomian glands present in the sub palpebral conjnctiva arranged in parallel position along the upper and lower eyelids of the eye each gland opened besides the hair follicle (cilia) and its secretion are oily (lipid) called miebum. This material very important to spreading the tear on the cornea to prevent evaporation and reaching the nutrients and oxygen to the cornea of the eye. In conclusion this study revealed the importance of the miebomian gland in the healthy status of the eye, in local Iraqi goats.